2020
DOI: 10.5021/ad.2020.32.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Pruritus according to Morphological Phenotype of Psoriasis and Association with Neuropeptides and Interleukin-31

Abstract: Background: Pruritus is a common symptom in psoriasis. However, few studies have assessed the characteristics of pruritus according to morphological phenotypes of psoriasis. Objective: To investigate the characteristics of pruritus according to morphological phenotypes of psoriasis and to assess the association with inflammatory mediators related to pruritus. Methods: Psoriasis patients were divided into 2 groups according to clinical phenotype: eruptive inflammatory (EI) and chronic stable (CS). Clinical data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Pruritus defined as an unpleasant sensation that provokes a desire to scratch was observed in 93% of all patients in our study. In other research, this phenomenon was reported with a frequency of 63–98% [ 14 , 15 , 16 , 17 , 18 , 19 ]. These differences may be due to regional features, the clinical characteristics of patients, and the divergent study methodologies used in other centers.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Pruritus defined as an unpleasant sensation that provokes a desire to scratch was observed in 93% of all patients in our study. In other research, this phenomenon was reported with a frequency of 63–98% [ 14 , 15 , 16 , 17 , 18 , 19 ]. These differences may be due to regional features, the clinical characteristics of patients, and the divergent study methodologies used in other centers.…”
Section: Discussionmentioning
confidence: 91%
“…In our study, there was no relationship between the subtypes of psoriasis and the frequency of pruritus. Compatible results were observed by Sung-Min Park with his group, albeit assessment was performed only in guttate and plaque subtypes [ 16 ]. Similarly, Szepietowski et al, Yosipovitch et al, and Bahali et al found that the presence of itch did not depend on the type of psoriasis, although the number of considered clinical subtypes were limited [ 18 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of previous studies on correlation between pruritus and Ps severity have been conflicting with some showing no correlation and others showing significant correlation. 28,[32][33][34]…”
Section: Discussionmentioning
confidence: 99%
“…The expression of NPY in psoriatic skin has yet to be evaluated. However, NPY levels in the serum of patients with psoriasis are not different from those of healthy volunteers ( Table 1 ) ( 65 ). Despite the lack of as association between NPY levels in circulation and disease status, decreased NPY levels are observed in the plasma of psoriatic patients with pruritis in comparison to those without pruritis ( 93 ), and activation of NPY signaling intrathecally can attenuate both mechanical and histaminergic itch in mice ( 94 ).…”
Section: Expression Of Npy Protein In Skin Pathologymentioning
confidence: 99%